Weaving Together a Global Civilization that Nurtures Justice and Peace: A Vision for Muslim Educators at Indonesia’s UIN Institutions - Martha C. Beck (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
This paper links the religious pluralism of Pancasila, Indonesia’s political ideology, with numerous ancient and contemporary worldviews, including Erwin Lazlo’s Systems View of the World, the “Functionalism” of Paul Davies and Richard Feynman, both theoretical physicists, and Aristotle. It gives extensive descriptions of Aristotle’s virtues: self-control, courage, even-temperedness, wise ambition, appropriate pride, a sense of humor, self-knowledge, sociability, justice, moderation in wealth, good judgment about what sorts of laws will weave people together in positive ways, including how to distribute social goods, how to punish law-breakers, and how to apply laws to specific cases within a context of the integration of nature and culture.  It then explains how Confucius, Buddha, Muhammad and Jesus either exercised those virtues throughout their lives or held those with power accountable for using power to promote human well-being. It explains Aristotle’s model for childhood education as a process of habituation from childhood on that integrates the moral and intellectual virtues throughout life. The paper makes suggestions for how to use the stories of these great spiritual leaders to structure a comprehensive system of integrated education. The paper explains how this model is compatible with the United Nations’ Capabilities model for development. Using this model of integrated education, members of all the world’s religions and humanists of all types can work together toward world peace.